2015
DOI: 10.3390/jfb6030917
|View full text |Cite
|
Sign up to set email alerts
|

Substrates for Expansion of Corneal Endothelial Cells towards Bioengineering of Human Corneal Endothelium

Abstract: Corneal endothelium is a single layer of specialized cells that lines the posterior surface of cornea and maintains corneal hydration and corneal transparency essential for vision. Currently, transplantation is the only therapeutic option for diseases affecting the corneal endothelium. Transplantation of corneal endothelium, called endothelial keratoplasty, is widely used for corneal endothelial diseases. However, corneal transplantation is limited by global donor shortage. Therefore, there is a need to overco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 137 publications
(233 reference statements)
0
55
0
1
Order By: Relevance
“…Transplanting the LC with the epithelial side down resulted in a more rapid recovery and a transparent cornea at 6 months when compared with control eyes. LC has also been used successfully as a scaffold for the expansion of both limbal epithelial stem cells and HCEnC in vitro (Kopsachilis et al, ; Lachaud et al, ; Navaratnam et al, ; Yoeruek et al, ). These data suggested that LC could eventually be used for human transplantation, but prior to in vivo use, further characterization is required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transplanting the LC with the epithelial side down resulted in a more rapid recovery and a transparent cornea at 6 months when compared with control eyes. LC has also been used successfully as a scaffold for the expansion of both limbal epithelial stem cells and HCEnC in vitro (Kopsachilis et al, ; Lachaud et al, ; Navaratnam et al, ; Yoeruek et al, ). These data suggested that LC could eventually be used for human transplantation, but prior to in vivo use, further characterization is required.…”
Section: Discussionmentioning
confidence: 99%
“…The two delivery systems have been described, namely, (a) an intracameral injectable endothelial cell suspension, or (b) tissue‐engineered endothelial grafts utilizing a carrier membrane or scaffold. Culturing the cells on a scaffold resembles the current endothelial surgical techniques, and as such, the majority of research groups involved in this domain are investigating the scaffold‐based approach (Navaratnam, Utheim, Rajasekhar, & Shahdadfar, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The corneal endothelium layer maintains corneal transparency by balancing its hydration through barrier and pump functions [1,2]. Damage of the hexagonal-shaped corneal endothelial cells (CECs) can cause severe visual impairment and can even lead to blindness [3].…”
Section: Introductionmentioning
confidence: 99%
“…32 Meanwhile, mature CECs can also provide some inducing factors for undifferentiated CECs by autocrining some regulatory factors. 33,34 At this stage, we induced the differentiation of POMPs using a mixed-conditioned medium of both LEC-CM and HCEC-CM. The morphologic changes of cells were documented by light microscopy (Fig.…”
Section: The Isolation and Characterization Of Cec-like Cellsmentioning
confidence: 99%